Development of a framework of an integrated river catchment management plan for Sungai Maong watershed - Norina, Ak Frederick Sambang. (2001)
Lacking of integrated catchment management is the major factor leading to the deterioration of Sg Maong water quality. This is worsening because of rapid development in the catchment. Based on WQI, Sg. Maong is classified into Class III and IV. In this project, framework of integrated catchment management plan for Sg.Maong is develop. Literature search, field observation, and in-depth interview were the methadologies used for collecting baseline data.